Sosialisasi dan Pendampingan SK Nomor 0424/I/BS.00.01/2022 tentang Ejaan Bahasa Indonesia yang Disempurnakan untuk Perbaikan Tata Kelola Persuratan bagi Perangkat Desa di Kabupaten Magelang - Sri Hastuti; Kundharu Saddhono; Budhi Setiawan; Muhammad Rohmadi; Raheni Suhita; Ani Rakhmawati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The enactment of Law No. 24 of 2009 concerning Flags, Languages and State Symbols and the National Anthem which is confirmed by PP No. 57 of 2014, Minister of Education and Culture Regulation No. 42 of 2018, and SK No. 0424/I/BS.00.01/2022, of course, must be obeyed by all Indonesian citizens. Governance of correspondence in government agencies is one that is regulated in the law, in particular Article 33 paragraph 1 which reads "Indonesian must be used in official communication in government and private work environments". Meanwhile, linguistic problems, such as spelling errors, word choice errors, sentence meaning errors, sentence composition errors, are rarely considered. There are many versions of letters sent by government agencies, especially at the village/kelurahan level. There are many variations and there is no standard one related to this correspondence because government officials do not yet have standard guidelines. There are so many mistakes made by government officials in making official letters. The target group for this community service is the sub-district in Donorojo Village, Mertoyudan District, Magelang Regency, Central Java Province which consists of 12 hamlets. This community service program will be carried out in three stages, namely planning, implementation, and evaluation. The implementation of the program is planned to last 6 months starting in mid-2023. This implementation begins with planning, implementation, and ends with evaluation.